1996
DOI: 10.1097/00005373-199607000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes after Lower Extremity Trauma

Abstract: Previous studies have shown that over one-quarter of patients who were working before a severe lower extremity fracture had not returned to work by 12 months after injury. Disabilities also persisted in household management, recreation, and social interaction. The objective of this study was to determine whether recovery extended beyond 12 months. Three hundred nineteen patients who were previously working and were treated at three level I trauma centers for a severe lower extremity fracture were prospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(64 citation statements)
references
References 12 publications
3
60
0
1
Order By: Relevance
“…However, complicated injuries, unless treated appropriately, may cause serious loss of function, and this may lead to considerable disability and reduced life quality. [6,7] In the structure of various centers, there are two different rooms, namely an intervention room for plastic surgery and an operation theater. In the event there is no life-threatening situation and repair under local anesthesia is possible, many patients can be treated in the intervention room.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, complicated injuries, unless treated appropriately, may cause serious loss of function, and this may lead to considerable disability and reduced life quality. [6,7] In the structure of various centers, there are two different rooms, namely an intervention room for plastic surgery and an operation theater. In the event there is no life-threatening situation and repair under local anesthesia is possible, many patients can be treated in the intervention room.…”
Section: Discussionmentioning
confidence: 99%
“…However, injuries related to plastic surgery may result in considerable disability and loss of life quality. [6,7] Our review of the literature revealed a few studies in which the issues within the field of interest of emergency plastic surgery, such as upper extremity surgery, head-and-neck traumas, and soft tissue traumas, were examined individually; however, no publication involved every field of practice of emergency plastic surgery. Therefore, retrospectively reviewing 10,732 patients admitted to the Emergency Plastic Surgery Department in Şişli Etfal Training and Research Hospital between 2000 and 2004, we aimed to construct a reference study stressing the significance of emergency plastic and reconstructive surgery in trauma centers.…”
Section: Ocak -January 2011 Ulus Travma Acil Cerrahi Dergmentioning
confidence: 99%
“…When asked if there were any additional items to consider including in the FIX-IT measure, 2 reviewers suggested including return to work, a patient-important outcome that indicates the ability to resume both physical and mental activities. 17 As a substantial proportion of patients will not return to work even 2 years after the fracture occurrs, 18 return to work as a measure of fracture healing may not be very responsive to change. 17 Therefore, the developers opted not to incorporate questions on return to work.…”
Section: Assessment Of Face and Content Validitymentioning
confidence: 99%
“…Although adequate surgical treatment might restore full function and quality of life, there remains a finite risk of permanent deficit as well as the risk of a complication during the course of healing 1,2 . The risk of permanent deficits or complications depends on fracture characteristics, patient-related risk factors, and treatment-specific complications [3][4][5][6][7] .…”
mentioning
confidence: 99%